2015
DOI: 10.1121/1.4906266
|View full text |Cite
|
Sign up to set email alerts
|

The effects of delayed auditory and visual feedback on speech production

Abstract: Monitoring the sensory consequences of articulatory movements supports speaking. For example, delaying auditory feedback of a speaker's voice disrupts speech production. Also, there is evidence that this disruption may be decreased by immediate visual feedback, i.e., seeing one's own articulatory movements. It is, however, unknown whether delayed visual feedback affects speech production in fluent speakers. Here, the effects of delayed auditory and visual feedback on speech fluency (i.e., speech rate and error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…These results reinforce reports from students who described difficulties in speaking fluently with DAF (15,28) . In the intergroup comparison of spontaneous speech, there were more differences in Non-Altered Auditory Feedback condition than in the delayed one (Tables 2).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These results reinforce reports from students who described difficulties in speaking fluently with DAF (15,28) . In the intergroup comparison of spontaneous speech, there were more differences in Non-Altered Auditory Feedback condition than in the delayed one (Tables 2).…”
Section: Discussionsupporting
confidence: 81%
“…As the main focus of Speech-Language Pathology intervention in cluttering is the speech rate reduction and the fluency promotion, and these are the most frequently found effects in DAF (15,(17)(18)(19)(20)(21)(22)(23)(24) , it becomes relevant to investigate the effects of delayed auditory feedback on the cluttering individuals' speech. Will the greater cortex activation in people who clutter also increase the fluency?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in fluent individuals have shown that delayed auditory feedback (DAF) has caused difficulties in speech fluency [16][17][18][19][20][21][22] , and decrease in speech rate [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…An important tool used by speakers to maintain fluency during oral task is the auditory feedback of the continuous flow of speech 11 . The advent of technology has promoted an increase in researches that can help the intervention in stuttering therapy, for example, the use the altered auditory feedback 12 .…”
Section: Introductionmentioning
confidence: 99%